THE WAYANG GOLEK BROADCAST PROGRAM AS A STRATEGY EMPLOYED BY MAJA FM COMMUNITY RADIO TO PRESERVE CULTURAL EXISTENCE - Hendra Prasetia; Irfan Haniful Qoyyim; Zaenal Mukarom; Encep Dulwahab (Jurnal Mahasiswa Antropologi dan Sosiologi Indonesia (JuMASI), 2026)
The rapid development of digital technology has significantly influenced the sustainability of traditional arts in Indonesia, including Wayang Golek as one of the most important cultural icons of Sundanese heritage. Amid changing media consumption patterns and declining public interest, innovative cultural preservation strategies are required to ensure the continuity of this traditional performance art. This study examines the cultural preservation strategy implemented through the "Sayang Golek" program on community radio, which seeks to revitalize Wayang Golek by integrating cultural communication, local language preservation, digital adaptation, and active community participation. Employing a qualitative case study approach, the research analyzes the implementation of local cultural broadcasting programs through interviews, observations, and document analysis. The findings indicate that community radio functions as an effective platform for strengthening cultural identity and increasing public engagement with traditional arts. By combining conventional broadcasting with digital dissemination and participatory communication, the program creates an adaptive model of cultural mediation that expands audience reach while preserving local values. The study concludes that community radio remains a relevant and strategic medium for safeguarding intangible cultural heritage and promoting the sustainable revitalization of Wayang Golek in the digital era.